Embodiment in 18th Century Depictions of Human-Machine Co-Creativity - Kantosalo, Anna; Falk, Michael; Jordanous, Anna (Frontiers in Robotics and AI, 2021)
Artificial intelligence has a rich history in literature; fiction has shaped how we view artificial agents and their capacities in the real world. This paper looks at embodied examples of human-machine co-creation from the literature of the Long Eighteenth Century (1650-1850), examining how older depictions of creative machines could inform and inspire modern day research. The works are analysed from the perspective of design fiction with special focus on the embodiment of the systems and the creativity exhibited by them. We find that the chosen examples highlight the importance of recognising the environment as a major factor in human-machine co-creative processes and that some of the works seem to precede current examples of artificial systems reaching into our everyday lives. The examples present embodied interaction in a positive, creativity-oriented way, but also highlight ethical risks of human-machine co-creativity. Modern day perceptions of artificial systems and creativity can be limited to some extent by the technologies available; fictitious examples from centuries past allow us to examine such limitations using a Design Fiction approach. These examples vividly capture some of the ideals concerning creativity support and co-creativity during the time, which can be used as inspirations for future work.